ANALISIS PRODUKTIVITAS PEMBANGKIT LISTRIK TENAGA GAS DENGAN METODE OBJECTIVE MATRIX (OMAX) (Studi Kasus : PT SA ARY INDORAYA) - Hardiantara, Yuda; Kusmindari, Ch Desi; Zahri, Amiluddin (Direktorat Riset dan Pengabdian pada Masyarakat Universitas Bina Darma, 2019)
Electricity demand in Indonesia is growing to encourage companies to manage resources effectively and efficiently in order to improve performance and target achievement. Analyzing the productivity index aims to determine the productivity of the benchmark electricity production in the achievement of the company. The results of this study is the productivity index of electricity production period of December 2016 every week that is 163.7, 245.2, 85.08, 57.96, while the period of January 2017 every week is 103.98, 216.18, 269.16, 162.48, ratios that affect the productivity of the production of electric power plant based on order of importance is the ratio of 1 (total production / hours of operation machine) with a weight of 3:22, a ratio of 2 (total electricity production / total number of employees) with a weight of 26.1, a ratio of 3 (the number of gas consumption / total power production) with a weight of 18:58, a ratio of 4 (total electricity consumption own / total power production) with a weight of 10:32, and a ratio of 5 (the total number of employees / number of absent workers) with a weight of 5.76, the lowest value ratio is the ratio of six (the number of hours the engine die / the number of engine operating hours) with a weight of 4:02.